Effect of sex Linked dwarfing gene (dw) on Normal-grown Ballade hens produced in hens owns the dwarf gene (dw-) on productive efficiency (Journal of Hama University, 2022)
Normal-grown Ballade hens (DW-) and Normal-grown Ballade hens produced by intermarrying Normal-grown rooster (DWDW), and hens which have a recessive sex Linked dwarfing gene (dw-), were cared in cages in a coop of the open model. The results indicate that the age of sexual maturity of Normal-grown Ballade hens (DW-) produced by dwarf hens (dw-) was no significantly. It has decrease 4 days compared to hens produced by Normal-grown hens (DW-). The Normal-grown Ballade hens produced by dwarf hens (dw-) during the egg production period from 21 to 37 weeks showed an increase in the average daily egg production by 0.04 eggs per day per hen (p